A system study on the manufacturing process of Nlite Fiberglass and Design, Inc. - Cruz, Ericson Lance Mirafelix (Animo Repository, 2022)
Nlite Fiberglass & Design, Inc. (NFDI) is a roofing material manufacturing company under its parent company, Naturalite Industrial Corporation. In the year of 2009, the company was officially established to cater to the increasing demand of its construction services and products. The products and services offered by the company are LOLITE Glass Reinforced Plastics, Polycarbonate Skylight Roofing, Steel Fabrication and Design, Standard and Custom Basketball Goals, and Pre-cut Fiberglass Roofings. Among these products, the main product of the company is the Pre-cut Fiberglass Roofings. After completing the documentation of the company’s present system, a SWOT analysis was performed to evaluate the current situation of the company. The importance of each identified problem of the company was then assessed through the WOT-SUG analysis. The average rate of returns due to defects from January 2020 to December 2020 is 0.54%, which incurred a total cost of P161,967.95. This problem was identified as the most important and considered to be the problem statement of the study. For the problem statement, an initial why-why diagram was developed to investigate the possible root causes of the problem. After the validation and verification of each root cause, the final why-why diagram was determined where the root causes of the problem were identified to be Cutter Operator Grinds at Wrong Point, Transport Mishandling from Cutting & Grinding Stage to Stacking Area, Lay-upping Pattern and Pressure Discrepancy within Labor Pair, and Current In-Process Verification of 16ft Panels Causes Ocular Fatigue. Based on these root causes, alternative solutions were generated and selected through the Kepner-Tregoe Decision Analysis. The selected alternative solutions are the Conversion of Tables into Modified Cutting & Grinding Tables, Implementation of 5S Policy, Addition of Error-proofing Procedures for Hand Lay-up Process, and Implementation of New Policy for Monitoring the Thickness Quality. A cost-benefit analysis was performed to quantify the financial upside and downside in the implementation of the proposed alternative solutions. With the initial investment cost of ₱160,362.00, yearly cost of ₱36,800.00, and yearly benefit of ₱187,213.19, the company is estimated to receive a yearly inflow of ₱150,413.19. In calculating the net present value contribution over a five year period, the company will benefit from these solutions with a total net present value contribution of ₱548,604.48. The payback period of the proposed system was also computed, which had the time period of 1.0661 years or 12.80 months.